2022
DOI: 10.3390/diagnostics12071584
|View full text |Cite
|
Sign up to set email alerts
|

Development of a New Index to Distinguish Hepatic Encephalopathy through Automated Quantification of Globus Pallidal Signal Intensity Using MRI

Abstract: Hyperintensities within the bilateral globus pallidus on T1-weighted magnetic resonance images were present in some liver cirrhosis patients with hepatic encephalopathy. The symptoms of covert hepatic encephalopathy are similar to those of mild dementia. We aimed to develop a new diagnostic index in which to distinguish hepatic encephalopathy from dementia. The globus pallidus signal hyperintensity was quantified using three-dimensional images. In addition, the new index value distribution was evaluated in a c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 25 publications
0
1
0
Order By: Relevance
“…Accordingly, magnetic resonance imaging studies of brains of people with MHE/CHE have shown alterations in white matter, particularly in the frontal lobes, as well as edema in the basal ganglia 23 . Other work has found signal changes in the globus pallidus, which is instrumental in efficient decision‐making, 24 particularly inhibition 25 . Similarly, a previous physiologic study has shown that reaction time and response accuracy evaluated by an electroencephalogram were worse in patients with MHE/CHE than in controls 26 .…”
Section: Discussionmentioning
confidence: 99%
“…Accordingly, magnetic resonance imaging studies of brains of people with MHE/CHE have shown alterations in white matter, particularly in the frontal lobes, as well as edema in the basal ganglia 23 . Other work has found signal changes in the globus pallidus, which is instrumental in efficient decision‐making, 24 particularly inhibition 25 . Similarly, a previous physiologic study has shown that reaction time and response accuracy evaluated by an electroencephalogram were worse in patients with MHE/CHE than in controls 26 .…”
Section: Discussionmentioning
confidence: 99%